2012
DOI: 10.1371/journal.pone.0030804
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Evolution under Chemotherapy Pressure in 29 Breast Cancer Cell Lines Results in Dissimilar Mechanisms of Resistance

Abstract: BackgroundDeveloping chemotherapy resistant cell lines can help to identify markers of resistance. Instead of using a panel of highly heterogeneous cell lines, we assumed that truly robust and convergent pattern of resistance can be identified in multiple parallel engineered derivatives of only a few parental cell lines.MethodsParallel cell populations were initiated for two breast cancer cell lines (MDA-MB-231 and MCF-7) and these were treated independently for 18 months with doxorubicin or paclitaxel. IC50 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…17) In addition, a higher IC 50 value than ours has also been reported recently. 18) At around the IC 50 value obtained in our study (10 to 25 nm), thermo treatment was found to significantly enhance PTX-induced suppression of proliferation in MCF-7 cells. The dose of PTX administered clinically is generally calculated using bodysurface area.…”
Section: Discussionsupporting
confidence: 53%
“…17) In addition, a higher IC 50 value than ours has also been reported recently. 18) At around the IC 50 value obtained in our study (10 to 25 nm), thermo treatment was found to significantly enhance PTX-induced suppression of proliferation in MCF-7 cells. The dose of PTX administered clinically is generally calculated using bodysurface area.…”
Section: Discussionsupporting
confidence: 53%
“…Dysregulation of DNA repair system and its signaling to checkpoints of cell cycle is strongly associated with the predisposition to several cancers and affects responses to DNA-damaging anticancer therapy [11]. Tubulin alpha 1c, TUBA1C , was associated with chemotherapy resistance in breast cancer cell line [48]. EXOC1 from the gene expression model is a component of the exocyst complex and a multiple protein complex including this gene is vital to target exocytic vesicles to specific docking sites on the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…However, somatic mutations in tubulins have been investigated as a cause of taxane resistance (41). Leandro-Garcia and colleagues (29) have investigated the role of tubulin gene polymorphisms in TRSN using lymphocytes from peripheral blood samples from patients exposed to taxanes in various tumor types and found that polymorphisms in certain genes led to a reduction in susceptibility to TRSN.…”
Section: Discussionmentioning
confidence: 99%